Endoscopic trans-nasal removal of impacted bullet in the sphenoid sinus: a case report - Juwarna, Wijaya; Munir, Delfitri (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Foreign body of the sphenoid sinus is a rare condition and most of the documented cases are shrapnel wounds. The most cases of sinuses foreign bodies are in maxillary and frontal sinus. Very few cases have been reported of lodgment of foreign body in paranasal sinuses. Garces and Norris reported that 70% of these foreign bodies usually appeared after maxillofacial traumas and 30% appeared during or after dental procedures of maxilla. A bullet impacted in the sphenoid sinus case in nineteen-year-old man was reported involving the anterior skull base. The bullet was safely removed with the trans-nasal endoscopic approach preserving the structures around the sphenoid sinus. Proximity of the sphenoid sinus to vital structures such as the optic nerve and internal carotid artery may render life-threatening complications. Adequate knowledge of the anatomical variations with regard to the sphenoid sinus and good preoperative planning are essential to ensure safe removal of foreign bodies, thereby avoiding catastrophic complications.